Screening for thalassemia carriers among the Han population of childbearing age in Southwestern of China - Du, Yepei; Zhou, Cong; Wang, Jing; Yang, Yanting; Liu, Hui (Frontiers in Genetics, 2024)
Purpose: Thalassemia is a severe hereditary blood disorder that poses a significant threat to human health and leads to mortality and disability. It is one of the most prevalent monogenic diseases worldwide. The aim of this study was to analyze the molecular epidemiological data of individuals of childbearing-age from the Han ethnic group with thalassemia in Southwest China and to explore the application of next-generation sequencing (NGS) technology in screening thalassemia carriers.The participants were Han males and females of childbearing age who sought medical advice at the West China Second University Hospital, Sichuan University from June 2022 to June 2023. We detected α-and β-thalassemia mutations using full-length capture of the thalassemia genes and NGS technology. Results: In a cohort of 1093 participants, 130 thalassemia carriers were identified, with an overall detection rate of 11.89% (130/1093). Among these, 0.91% (10/1093) had mutations that could not be detected using traditional PCR techniques. The proportions of carriers with α-, β-, and α-complexed β-thalassemia gene mutations were 7.68% (84/1093), 3.93% (43/1093), and 0.27% (3/1093), respectively. We identified a novel HBA2 c.166del variant that has not been previously reported. Conclusions: Using NGS technology, we found that the mutation-carrying rate of thalassemia genes was 11.89% in the Han population of childbearing age in Southwest China.Compared with the results of traditional PCR techniques, NGS detected an additional 0.91% (10/1093) rare genetic variants. NGS technology should be utilized as the primary screening method for thalassemia carriers among Han nationality people of childbearing age in Southwest China.